The Efficacy and Safety of Xinjia Xuanbai Chengqi Granules in Acute Exacerbation of COPD: A Multicentre, Randomised, Double-Blind, Controlled Trial. (23rd June 2022) - Qi, Ruihan; Zhang, Hongchun; Li, Demin; Gao, Feng; Miao, Qing; Chen, Sheng; Huang, Yan; Wu, Lei; Lu, Zhenhui; Hu, Haibo; Li, Erran; Chen, Zhibin
Abstract : Purpose . The study aimed to explore the efficacy and safety of Xinjia Xuanbai Chengqi granules (XJXBCQ) combined with conventional medicine in the treatment of acute exacerbation of chronic pulmonary disease (AECOPD). Patients and Methods . This multicentre, double-blind, parallel, placebo-controlled, randomised clinical trial conducted in China from January 2019 to February 2021 recruited 330 participants who were allocated into three groups. All participants underwent conventional basic treatment with oxygen therapy, antibiotics, and a bronchodilator. Besides, group A received XJXBCQ granules and budesonide suspension for inhalation; group B received XJXBCQ granules and half dosage of budesonide suspension; and group C received budesonide suspension and a placebo. All therapies lasted for 5 days, and participants were followed up for 30 days after discharge. The primary outcomes were efficacy, traditional Chinese medicine (TCM) syndrome score, and clinical symptom score. Secondary outcomes included the blood gas analysis, serum inflammatory markers, adverse events, mortality, theoretical discharge time, actual hospitalisation time, proportion of patients requiring invasive mechanical ventilation, proportion of patients transferred to an intensive care unit (ICU), and readmission rate within 30 days after discharge. Results . XJXBCQ adjunct with conventional treatment could significantly improve the total efficacy (P < 0.05 ). Meanwhile, group A showed significantly better results than group C in the TCM syndrome score, phlegm score, and Wexner constipation score (P < 0.05 ). For modified British medical research council (mMRC), on day 3 (−0.17, 95% confidence interval [CI]: −0.33–−0.01) and day 4 (−0.20, 95% CI: −0.39–−0.02), group A performed statistically better than group C . No significant differences in other secondary outcomes were detected. Conclusion . XJXBCQ is beneficial and safe for AECOPD treatment and could be considered an adjunctive therapy for promoting the relief of clinical symptoms. This trial is registered with ChiCTR1800016915 .